2021
DOI: 10.1530/ec-21-0172
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity with diabetic retinopathy in US adults with diabetes in a national survey

Abstract: Objective: There is a lack of consensus on whether a high body mass index (BMI) increases the risk of diabetic retinopathy (DR). We aimed to investigate the association between BMI, overweight, obesity, and DR using the data of diabetes respondents in the 2015 US Behavioral Risk Factor Surveillance System survey. Methods: Diabetes respondents aged over 18-year-old with complete information as well as undergone fundus examination in the past two years or had been diagnosed with DR were included. Weighted log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In several studies from multiple countries, there was no association between DR and measures of obesity [18,40,47,48]. Other studies have shown that increasing BMI or obesity measured using various metrics increased odds, especially among those who are obese, and, in some cases, obesity associated with more severe DR (PDR vs NPDR) [49][50][51][52][53]. However, in studies that had results showing positive association between obesity and DR the average BMI was usually higher than in our study population with sample means over 30 as compared to mean values ~26 in our Mumbai slum sample.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies from multiple countries, there was no association between DR and measures of obesity [18,40,47,48]. Other studies have shown that increasing BMI or obesity measured using various metrics increased odds, especially among those who are obese, and, in some cases, obesity associated with more severe DR (PDR vs NPDR) [49][50][51][52][53]. However, in studies that had results showing positive association between obesity and DR the average BMI was usually higher than in our study population with sample means over 30 as compared to mean values ~26 in our Mumbai slum sample.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies from multiple countries, there was no association between DR and measures of obesity (18,41,48,49). Other studies have shown that increasing BMI or obesity measured using various metrics increased risk, especially among those who are obese, and, in some cases, obesity associated with more severe DR (PDR vs NPDR) (50)(51)(52)(53)(54). However, in studies that had results showing positive association between obesity and DR the average BMI was usually higher than in our study population with sample means over 30 as compared to mean values ~26 in our Mumbai slum sample.…”
Section: Discussionmentioning
confidence: 99%
“…One such study, which concentrated on screening practices in Iran, discovered that the frequency of DR rose with age from 55 to 74 years 30 . According to research conducted in southern India, people aged 60 to 69 are the most frequent group to suffer from DR 34 .…”
Section: Discussionmentioning
confidence: 99%